Medicine, religion, and magic in early Stuart England : Richard Napier's medical practice - Hadass, Ofer, 1969- (Magic in history., 2018)
"Explores the work of the astrologer-physician and Anglican rector Richard Napier (1559-1634). Examines Napier's medical and magical practices in their larger context and shows how the physician incorporated both astral and ritual magic into his medicine"--Provided by publisher.